The effects of perceptual-cognitive training with Neurotracker on executive brain functions among elite athletes - Moen, F.; Hrozanova, M.; Stiles, T. (Cogent Psychology, 2018)
The current study tests possible transfer effects from NT 3D MOT training among elite athletes from dynamic sports on executive brain functions such as alerting, orienting executive control, inhibition, shifting and updating. Sixty athletes from different sports such as martial arts (boxing and wrestling), handball, soccer, orienteering, biathlon, alpine skiing, and Paralympic sports (sled hockey, badminton and table tennis), participated in a cross-over experiment-control group design over a period of 10 weeks. The results in the current study show specific training effects on training measures used by the NT 3D MOT tool, but no significant transfer effects on the executive functioning tests. The results are discussed based on the importance of training specificity and the mental state at the moment of NT 3D MOT training.